Pipeline pharmacogenetics: A novel approach to integrating pharmacogenetics into drug development - Akkari, Patrick; Swanson, T.; Crenshaw, D.; Grossman, I.; Sundseth, S.; Burns, D.; Roses, A. (2009)
There has been a decline in the number of new drugs registered over the past decade and regulatory concerns for safety as well as payer concerns for efficacy have focused attention on stratified medicine. Integration of pharmacogenetics into the drug development pipeline will contribute to the development of new stratified drugs. We describe here the concept of pipeline pharmacogenetics and its application throughout the phases of drug discovery. Pipeline pharmacogenetics enables the evaluation of the genetic contribution to safety potentially lowering barriers to registration as well as providing rationale for efficacy and enabling co-development of genetic in vitro diagnostics. © 2009 Bentham Science Publishers Ltd.